Current Value Accounting: Its Concepts and Practice at N.V. Philips Industries, the Netherlands (Book). - Meyer, Philip E.; Menon, Krishnagopal (The Accounting Review, 1983)
Reviews the book "Current Value Accounting: Its Concepts and Practice at N.V. Philips Industries, the Netherlands," by Adolf J.H. Enthoven.